Credit constraints and investment in human capital: training evidence from transition economies - Alexander Popov (European Central Bank (ECB), 2013)
Using a unique survey database of 8265 firms from 25 transition economies, I find that lack of access to finance in general, and to bank credit in particular, is associated with significantly lower investment in on-the-job training. This effect is stronger in education-intensive industries and in industries facing good global growth opportunities. To address endogeneity issues, I use the structure of local credit markets as an instrument for credit constraints at the firm-level. In addition, in panel estimates, I control for the presence of unobserved firm-level heterogeneity, as well as for changes in macroeconomic conditions.
Keywords: G10; J21; J24; M53; 330; credit constraints; human capital; on-the-job training